Effect of strain history on the monotonic and cyclic response of natural and reconstituted silts. Issue 160 (September 2022) - Dadashiserej, Ali; Jana, Amalesh; Stuedlein, Armin W.; Evans, T. Matthew
Abstract: The effect of strain history on monotonic and cyclic response of intact and reconstituted, low and high plasticity silt deposits have been investigated through a series of constant-volume, staged, stress- and strain-controlled cyclic direct simple shear tests. In many cases the specimens subjected to stress-controlled loading exhibited a progressive increase in cyclic resistance due to beneficial effects of increased density following post-cyclic reconsolidation, apparent pseudo-overconsolidation and presumably increased lateral stresses. Such effects outweighed the detrimental effects of fabric destructing as a result of the prior strain history. However, some specimens exhibited an inconsistent evolution of cyclic resistance when assessed using different shear strain cyclic failure criteria. Symmetric accumulation of shear strains in earlier shearing stages did not consistently result in an increasing trend in the post-cyclic resistance; additionally, increases or decreases in cyclic resistance can occur in subsequent shearing stages depending on the amplitude of the maximum shear strain. Staged, strain-controlled tests were used to investigate the cyclic soil response to small and large shear strains, the latter of which caused a reduction in the cyclic resistance of overconsolidated (OC) silt specimens in the following loading event, confirmed using shear wave velocity, V s, measurements which indicated substantial fabric disturbance following the large strain event. In contrast, normally-consolidated (NC) and OC specimens subjected to multiple stages of small cyclic shear strain exhibited progressive increases in V s, the magnitude of which varied with stress history. The increase in cyclic resistance in the NC specimens was related to increased pseudo-overconsolidation following reconsolidation. The monotonic undrained shear strength of all silt specimens subjected to staged cyclic loading increased following post-cyclic reconsolidation; the increase in strength and changes in volumetric tendencies are governed by the magnitude of post-cyclic reconsolidation and changes in soil fabric inferred from V s, respectively.